The Presence of Two Distinct Lineages of the Foot-And-Mouth Disease Virus Type A in Russia in 2013–2014 Has Significant Implications for the Epidemiology of the Virus in the Region - Victor V. Nikiforov; Sergey A. Noskov; Alexander V. Sprygin; Mohammad Abed Alhussen; Anastasia S. Krylova; Taisia V. Erofeeva; Svetlana N. Fomina; Svetlana R. Kremenchugskaya; Fedor I. Korennoy; Maxim V. Patrushev; Ilya A. Chvala; Tamara K. Mayorova; et al. (Viruses)
Molecular surveillance of FMD epidemiology is a fundamental tool for advancing our understanding of virus biology, monitoring virus evolution, and guiding vaccine design. The accessibility of genetic data will facilitate a more comprehensive delineation of FMDV phylogeny on a global scale. In this study, we investigated the FMDV strains circulating in Russia during the 2013–2014 period in geographically distant regions utilizing whole genome sequencing followed by maximum-likelihood phylogenetic reconstruction of whole genome and VP1 gene sequences. Phylogenetic analysis showed congruence in the topology of the phylogenetic trees constructed using the complete genome and VP1 gene sequence, clearly demonstrating that the isolates analyzed belong to two distinct genetic lineages: A/SEA97 in the Far East and Iran-05 in the North Caucasus. The A/SEA97 isolates exhibited a close genetic identity to those from China and Mongolia, whereas the Iran-05 isolates demonstrated clusterization with those from Turkey. The vaccine-matching studies with isolates from the Far East and North Caucasus revealed no antigenic homology with A/SEA-97 (r1 = 0.015–0.29) and A/Iran 05 (r1 = 0.009–0.17). The close genetic relationship of FMDV in the reported outbreak waves to those from neighboring countries indicates that animal movement could contribute to spillover and virus dispersal. The phylogenetic data reported here provide insight into the molecular epidemiology of FMD in the Eurasia region, elucidating the circulation pattern, molecular evolution, and genetic diversity, which is highly valuable for guiding vaccine designs and improving regional eradication policies.